2016
DOI: 10.1038/ejhg.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat size in Huntingtin alleles is associated with cancer prognosis

Abstract: The abnormal expansion of a ≥ 36 CAG unit tract in the Huntingtin gene (HTT) leads to Huntington's disease (HD), but has also been associated with cancer: the incidence of cancer is lower in HD patients than in age-matched controls, but HD-causing variants of HTT accelerate the progression of breast tumors and the development of metastases in mouse models of breast cancer. To investigate the relationship between HTT CAGs and cancer, data concerning 2407 women with BRCA1 or BRCA2 mutations that predispose to br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Detailed structural analysis showed that echinomycin induces deformation in the mismatched DNA duplex, allowing cooperative recognition of the T:T mismatch by a second echinomycin molecule. Sequences harboring multiple CAG/CTG repeats are prone to form intra-strand T:T mismatches and have been associated with increased cancer risk in the past ( 84 , 85 ). This recent finding may be useful in re-assessing the utility of echinomycin for detection of MMR-deficient cancers, possibly by leveraging the DNA binding-induced fluorescence quenching properties of echinomycin.…”
Section: Ligand-induced Structures Of the Dna Duplexmentioning
confidence: 99%
“…Detailed structural analysis showed that echinomycin induces deformation in the mismatched DNA duplex, allowing cooperative recognition of the T:T mismatch by a second echinomycin molecule. Sequences harboring multiple CAG/CTG repeats are prone to form intra-strand T:T mismatches and have been associated with increased cancer risk in the past ( 84 , 85 ). This recent finding may be useful in re-assessing the utility of echinomycin for detection of MMR-deficient cancers, possibly by leveraging the DNA binding-induced fluorescence quenching properties of echinomycin.…”
Section: Ligand-induced Structures Of the Dna Duplexmentioning
confidence: 99%
“…Additionally, we showed that wild-type HTT is involved in normal mammary gland development [ 12, 14, 15 ]. Moreover, we described an association between the size of CAG repeats in wild-type HTT and cancer prognosis [ 16 ], as well as decreased cancer incidence in the HD population [ 17 ]. In this review, we discuss the function of HTT during carcinogenesis, as well as the relationship between CAG repeats size and cancer incidence and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although smoking has been reported to be more frequent in presymptomatic HD gene carriers than in the general population, cancer incidence has been reduced in HD. Thion et al (2016) made an interesting observation, asserting that polyglutamine diseases showed a lower incidence of cancer, independently of the CAG length (even if the CAG expansion does not reach the incomplete or complete penetrance range). They found that also though the frequency of cancer may be inversely correlated to the number of CAG repeats (nCAG), a large nCAG might favor the progression and local spreading of some cancers, particularly breast tumors (Thion et al, 2016).…”
Section: Type Of Cancer Cases Expectedmentioning
confidence: 99%
“…Thion et al (2016) made an interesting observation, asserting that polyglutamine diseases showed a lower incidence of cancer, independently of the CAG length (even if the CAG expansion does not reach the incomplete or complete penetrance range). They found that also though the frequency of cancer may be inversely correlated to the number of CAG repeats (nCAG), a large nCAG might favor the progression and local spreading of some cancers, particularly breast tumors (Thion et al, 2016). This was supported by McNulty et al (2018) in their research report from 6540 subjects participating in the REGISTRY study of the European Huntington's Disease Network, one of the most extensive studies performed comparing cancer incidence in HD patients with the general population, observing lower rates of malignancy in the former group.…”
Section: Type Of Cancer Cases Expectedmentioning
confidence: 99%